Prospecção pesqueira de teleósteos de profundidade no talude de Pernambuco, Brasil - PIRES, Alessandra Maria Advincula (2020)
Few studies have been carried out to date on the deep-sea fauna of the northeast coast of Brazil, especially due to the lack of commercial fishing on these resources, in addition to the lack of exploratory scientific activities on the sea floor. Seeking to contribute to the knowledge about marine fauna in the northwest of the South Atlantic, this study records the occurrence of new species of teleosts in the continental slope of Pernambuco, analyzes the vertical distribution and formation of assemblages, evaluates the richness, diversity and dominance at different depths and reports information on the population structure and reproduction of the most abundant teleost (Physiculus kaupi). Between October 2014 and March 2018, 24 fishing surveys were carried out covering 30 fishing sets with longline and 38 sets with bottom traps at depths of 200 to 600 m. During the study, eleven species of teleosts were found, eight representing the first records for the coast of Pernambuco (Physiculus kaupi, Pontinus rathbuni, Antigonia capros, Conger esculentus, Dysommina rugosa, Gymnothorax maderensis, Gymnothorax conpersus and Gymnothorax polygonius) and three already known (Lopholatilus villarii Epinephelus niveatus and Lutjanus vivanus). Data on the new species recorded include the coordinates and depths of collection, meristic and morphometric characteristics and comments on the distribution of species worldwide. Classification and ordering analysis, using abundance as capture per unit of effort (CPUE) in number of individuals of eight species, were carried out from eighteen traps fishing sets performed from October 2014 to February 2018 (P. kaupi, G. maderensis, G. polygonius, G. polygonius, G. conspersus, C. esculentus, P. rathbuni, A. capros and L. vivanus). The results indicate the teleosts found are common in deep water, except for L. vivanus and moray eels, which can be found, respectively, above 200 m and only in tropical and subtropical regions. There was no clear formation of assemblages among the species in terms of relative abundance by depth, but a slight trend that indicates the a transition zone at 300 m depth, from where richness, diversity and dominance begin to decrease. The data on the population structure and reproduction of P. kaupi showed a higher proportion of females, particularly at shallower depths, with possible ontogenic migration in function of feeding and reproduction. Reproductive characteristics similar to several Gadiformes species and deep-sea species, as a continuous spawning, asynchronous ovarian development and low average fertility was also observed in P. kaupi. The first maturation size for P. kaupi females was estimated at 17.9 cm total length. The results provide a baseline which allows the monitoring of future changes in the structure and diversity of the depth teleosts population that occurs in the continental slope off Pernambuco.